تناول سوسيولوجي لتكوين المورد البشري في المؤسسة الجزائرية - فرفار, سامية (جامعة الوادي - University of Eloued, 2022)
نهدف من خلال هذا المقال إلى تسليط الضوء على إشكالية تكوين المورد البشري في المؤسسة الجزائرية، هذا المورد الذي يعد المحرك الأساسي و المحوري لأي مؤسسة مهما كانت طبيعة نشاطها؛ الأمر الذي يتطلب تقديم عناية و اهتمام كبيرين بالمورد البشري من خلال الرفع من قدراته و مهارته و تحديث معارفه باستمرار و تأهيله لأداء مهامه بطريقة جيدة. وهذا لن يتأتى إلا من خلال عملية التكوين التي تعتبر أحد أهم الوظائف الأساسية التي يتوقف عليها نجاح أي مؤسسة لا سيما في ظل التغيرات الاقتصادية و الاجتماعية و التكنولوجية التي جعلت العمل أكثر تعقيدا يتطلب مهارات فنية و تقنية عالية؛ تستوجب إكساب الفرد المهارات و الخبرات العلمية و جعله أكثر مرونة و تكيفا مع ظروف العمل المختلفة بما يساهم في الرفع من دافعيته في العمل. Abstract: We aim through this article to deal with the problem of human resource formation in the Algerian company, this resource which is the main driving force and pivot of any institution, whatever the nature of its activity. This requires giving great care and attention to the human resource by increasing their abilities and skills, constantly updating their knowledge and rehabilitating them to perform their tasks well. This will only come through the training process, which is one of the most important basic functions upon which the success of any institution depends, especially in light of the economic, social and technological changes that have made work more complex and require high practical and technological skills. Which requires individuals to get scientific skills with expertise to make them more flexible and adaptable to different working conditions, and this helps to increase their motivation at work.
مقال
Keywords: التكوين ; المورد البشري ; المؤسسة الجزائرية; Training; Human resource; Algerian company